2016
DOI: 10.3198/jpr2015.09.0058crg
|View full text |Cite
|
Sign up to set email alerts
|

Registration of PR1146‐138 Yellow Bean Germplasm Line

Abstract: The yellow bean (Phaseolus vulgaris L.) is an important market class in Haiti. There have been, however, no previous attempts to genetically improve this seed type for the Caribbean. Landrace varieties of yellow beans in Haiti are susceptible to Bean golden yellow mosaic virus (BGYMV) and Bean common mosaic virus (BCMV), which are important dry bean diseases in the region. In addition, leafhopper (Empoasca kraemeri Ross and Moore) can cause significant yield loss, especially when common beans are planted durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Yellowstone, tested as MSU yellow bean breeding line Y16507, was developed from a cross of PR1146‐123/Y11405. PR1146‐123 was a determinate yellow bean breeding line from the University of Puerto Rico program that possessed resistance to Bean golden mosaic and BCMV and is a sibling of the germplasm release PR1146‐138 (Beaver et al, 2016). Y11405 was a determinate yellow bean originally coded FR‐07‐AZP‐14‐06.…”
Section: Methodsmentioning
confidence: 99%
“…Yellowstone, tested as MSU yellow bean breeding line Y16507, was developed from a cross of PR1146‐123/Y11405. PR1146‐123 was a determinate yellow bean breeding line from the University of Puerto Rico program that possessed resistance to Bean golden mosaic and BCMV and is a sibling of the germplasm release PR1146‐138 (Beaver et al, 2016). Y11405 was a determinate yellow bean originally coded FR‐07‐AZP‐14‐06.…”
Section: Methodsmentioning
confidence: 99%
“…Locally released cultivars such as 'Morales' show less leafhopper damage. The yellow bean germplasm line PR1146-138 was identified in Haiti to have good levels of resistance to leafhoppers (Beaver et al, 2016b). The pinto bean germplasm line TARS-LH1 was screened in Puerto Rico for resistance to leafhoppers (Porch et al, 2020).…”
Section: Leafhoppersmentioning
confidence: 99%
“…However, determinate Andean common beans can suffer higher yield losses due to leafhopper pressure (Murray et al, 2001). Recently, PR1146-138, a determinate-habit yellow bean germplasm, was identified that may represent the first released Andean common bean germplasm with E. kraemeri leafhopper resistance (Beaver, Prophete, Démosthène, & Porch, 2016).…”
Section: Introductionmentioning
confidence: 99%